Faculdade Zumbi dos Palmares: uma proposta de Black College no Brasil do século XXI? - Santos, Hasani Eliotério dos (2020)
Zumbi dos Palmares College (FAZP) is an important private and communitary/non-profitable higher educational institution, and it was built objectively, but not exclusively, for black people’s inclusion in the Brazilian high education. This research analyse FAZP related to the tensions, conflicts, struggles and disputes which involve the process of institutionalization of this college. This dissertation is oriented by the following questions: What characteristics enable an analysis about FAZP under a transnational reading, which comprehend it as a Brazilian Historically Black College and University (HBCU)? How far is FAZP’s institutional model aligned with a professional and vocational higher education project like Booker T. Washington’s institutional and educational model? How was possible to institutionalize and to make possible the FAZP’s midiatic visibility at the racist Brazilian context? The methodology fully employed is based on bibliographic and documental research, analyse and description of articles’ images about FAZP, and also for the use of field research and the documentation of informal reports conceived by available attending actors at the FAZP’s meeting’s and events. The theoretical resource of this research is backed up by Cultural Studies and Post-Colonial authors, considering, specifically, the education as perennial field for the black diaspora’s creative and political agency. The research’s conclusons is that FAZP updates at the 21st century, by the multiculturalism and diversity’s political agenda at the corporative and entrepreneurial field, the initiative of black people’s higher education inclusion similar to Tuskegee Institute institutional model, designed by Booker T. Washington at the 20th century. This initiative has the main goal of provide vocational and professional formation for black youth, including the incentive of black entrepreneurship.